PERAN KECERDASAN EMOSIONAL (EQ) DALAM PEMBELAJARAN: STUDI LITERATUR DARI PERSPEKTIF PSIKOLOGI PENDIDIKAN - Yudi Hendrilia; Muhammad Sukron Fauzi; Dwi Hadita Ayu; Archristhea Amahoru; Septi Fitriana (LPPM Universitas Ekasakti, 2024)
This study aims to examine how technology integration in curriculum management and administration can contribute to improving the efficiency and effectiveness of school operations. This type of research is a literature study. Literature study is an important step in research that helps researchers to find out what has been previously studied on the same topic. The results of this study indicate that technology plays a crucial role in curriculum management and educational administration. Technology integration, such as learning management systems (LMS) and school management information systems (SMS), not only improves operational efficiency but also strengthens collaboration between teachers, students, and parents. With real-time data access and analysis, decision making becomes faster and more precise, allowing for more effective responses to student needs. Although challenges such as resistance to change and infrastructure problems remain, the long-term benefits of implementing technology are clear, including improving the quality of education and student readiness to face future challenges.